Contexto y pautas de intervencion de tecnologia fotovoltaica en edificios de la region NEA - Gallipoliti, Virginia A. (Universidad Nacional del Nordeste. Facultad de Arquitectura y Urbanismo. Instituto de Investigaciones Tecnológicas para el Diseño Ambiental del Hábitat Humano, 2022)
One of the most important renewable energy technologies for the production of electrical energy is that corresponding to photovoltaic solar systems, which is based on the direct transformation of solar radiation into electrical energy, through the photovoltaic effect. This work details the basic principles of the integration of photovoltaic systems into buildings, providing a global vision of the concept for future installations in the NEA region, while also looking at the current context of political, social and social aspects. of infrastructure in the region. The various reports emanating from national government entities and international reports, local, foreign experiences and ongoing research projects from national organizations were used as reference material. It is concluded that, despite the incipient participation of renewable energies in the energy matrix of the provinces of the region, the potential in renewable resources is high which leads to progress towards the expansion of electricity generation, which represents a great challenge logistics and management for current governments.